The Process of Building Tools for Evaluating Professional Skills - Nguyen, Thị Môn (Journal of Technical Education Science, 2008)
The exact evaluation of the learners' vocational skills to ensure an agreement between the training organizations and the labour users is necessary in the teaching practice at technical training universities. For this purpose, the following six steps are needed for the building of evaluation tools: 1. Defining the situation or problem we need to evaluate. 2. Defining the work or skills we need to evaluate. 3. Listing the materials, tools and equipment needed for the evaluation. 4. Establishing the standards for the performance of those skills. 5. Selecting the evaluation strategies. 6. Making the evaluation tools according to a definite regulation.